Enhancing Business Performance through Social Media Platforms Amid the COVID-19 Pandemic: A Study on Shopee in Malaysia - Kia Hui Gan; Abhijit Das; Vivekka Puvaneswaran; Parindran Rajandran; Zhichai Cheng; Zhengang Li; Salem Alothman; Nojoud Almutairi (Journal of the Community Development in Asia (JCDA), 2022)
Since corona-virus disease (COVID-19) has caused a major economic shock, entrepreneurs such as small business owners, agents, and drop shippers face enormous obstacles to carry out their businesses. This study aims to investigate the extent of social media platforms such as Youtube, Facebook, and Instagram in attracting customers towards Shopee, leading its business performance. This brief discusses how the COVID-19 crisis is accelerating an expansion of e-commerce especially Shopee towards customers, likely involving a long-term shift of e-commerce transactions from luxury goods and services to everyday necessities in conjunction with driving users' satisfaction, leading to business performance improvements. An online survey questionnaire is used for data collection and the respondents consist of a total of 150 Shopee users (buyers) from Malaysia. The findings of this study serve a valuable insight and guidelines for businesses to integrate into social media platforms for effective marketing as well as potential future development.Keywords: Business performance, COVID-19, E-commerce, Entrepreneurs, Shopee, Social media.